Legal Protection Copyright of Non-Fungible Token-Based Painting Works (NFT) in Indonesia - Yustisio, Rifki; Asshidiq, Abdullah Widy; Wafi, Muhammad Syafiq (Pusat Pengkajian Pancasila dan Konstitusi (PUSKAPSI) FH UNEJ, 2023)
In the midst of increasingly massive digitalization and modernization, the use of technology and information in producing masterpieces has brought new problems, one of which is related to digital-based copyright protection. In the background of this, this research then produces 2 (two) problem formulations that need to be researched, namely: how is the protection of copyright of Non-Fungible Token (NFT) based paintings in Indonesia? And what are the obstacles in the protection of copyright of Non-Fungible Token (NFT) based paintings in Indonesia?. This research is empirical research, with a sociological approach research method. The results showed that, Non-Fungible Token (NFT) as a digital work of art, civilly categorized as